Public Administration in the Field of Using and Protecting Land Resources: International Experience and Ukrainian Realities (Law and Safety, 2020)
The generalized experience of management in the field of using and protecting land resources in such countries as Denmark, Canada, Latvia, Germany, Poland, the USA, Switzerland, France and others, as well as features of management realization of this sphere in Ukraine have been considered.The purpose of the article is to determine the possibility and feasibility of introducing some elements of positive experience of management of developed countries into Ukraine in the field of use and protection of land resources.The methodological basis of the article is a set of general scientific and special research methods. In particular, the method of analysis allowed to study the features of the management of developed countries in the field of use and protection of land resources and to identify inconsistencies in the provisions of national legislation regulating land relations; The comparative legal method was used to compare foreign and Ukrainian experience of management in the field of use and protection of land resources, as well as the possibility of using certain measures aimed at the rational use of land in Ukraine.Two types of measures used in other countries to ensure the rational use and protection of land resources have been identified and considered: administrative (which are the form of implementation of state land policy and part of government activities) and economic (which are positive or negative incentives for land owners and users).The main problems that exist in the field of land management in Ukraine have been revealed. It has been emphasized that the State Service of Ukraine for Geodesy, Cartography and Cadastre performs at the same time diametrically opposed powers, which are conducive to corruption.It has been concluded that in order to ensure the rational use and protection of land resources, especially in the conditions of opening the land market in Ukraine, it is necessary to adopt the experience of more developed countries and make appropriate amendments to national legislation.
Keywords: land resources; agricultural lands; land market; circulation of agricultural lands; rational use and protection of lands; management in the field of land relations